Relevansi Maşlahah Al-Ghazali Terhadap Konteks Fikih di Indonesia - Saiful Badri (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2018)
Maṣlaḥah is considered important because all laws established by God contain elements of public benefit. Al-Ghazali firmly states that maṣlaḥah can be used as a legal proof (ḥujjah) under certain conditions. On the other hand, fiqh in Indonesia has its own distinctive characteristics that differentiate it from other traditions of fiqh. This study addresses three main questions: (1) What is al-Ghazali’s concept of maṣlaḥah? (2) What is the context of fiqh in Indonesia? (3) How relevant is al-Ghazali’s concept of maṣlaḥah to the context of fiqh in Indonesia? This research employs a library research method. The primary sources include al-Mustaṣfā min ‘Ilm al-Uṣūl by Abu Hamid al-Ghazali, Fiqh Nusantara: Methodology and Its Contribution to Strengthening the Unitary State of the Republic of Indonesia and the Development of the National Legal System by M. Noor Harisudin, and Fiqh Nusantara and the National Legal System from the Perspective of National Public Benefit by Zaini Rahman. Data were collected through documentation and analyzed using content analysis. The findings show: (1) According to al-Ghazali, maṣlaḥah is the preservation of the objectives of Islamic law (maqāṣid al-sharī‘ah), which consist of five essential elements. The use of maṣlaḥah mu‘tabarah as legal evidence falls under the category of qiyās, while maṣlaḥah mursalah must fulfill the conditions of necessity (ḍarūrah), certainty (qaṭ‘iyyah), and universality (kulliyyah). (2) Fiqh in Indonesia is a form of jurisprudence that develops and lives within Indonesian society, characterized by the acculturation of sacred texts with local cultural wisdom. (3) Al-Ghazali’s concept of maṣlaḥah, which is rooted in Sunni theology, is compatible with the context of the Indonesian Muslim majority who adhere to the Sunni tradition. Furthermore, his concept offers a rational and moderate framework that prevents the arbitrary use of maṣlaḥah as an independent legal basis. This compatibility demonstrates that the application of fiqh, especially the methodology of maṣlaḥah in Indonesia, finds strong relevance and minimal contradiction, thereby reflecting Islam as raḥmatan li al-‘ālamīn (a mercy to all creation).